Tendencias de los desarrollos teóricos de la ciencia económica. (2021)
The present article is about the evolution, the changes and the tendencies of the economic science in the last decades. In the micro-economic field begins to change the orthodox conceptions of considering the operation of the economic system as passive, stable and homeostático, or that it only fluctuates smoothly around some balance points and that it is just perturbed for the emergence of contingents and predictable exogenous crashes. Or, when considering the continuous and soft changes that experience the variables in the micro and macroeconomic model against the changes in the key variables of the global economy that take place in a discontinuous and unexpected way in the reality. From the new possibilities of the wide focus of the complexity, we meet with a fascinating world of concepts, terms and instruments that appear together, opening new horizons in almost all the fields of the knowledge: Dynamics, non “linealidad”, irregularity, order and chaos, they are some of them, behaving as them parts of a whole indivisible one. With relation to the field of macroeconomic study, the emergence of the new neoclassical macroeconomics represent, in certain may, the end of the economy of the State of Well-being. It goes from a focus where the dynamic intervention of the State is privileged toward one where its rol is minimized to the maintenance of the good conditions of competition, leaving of an evident superiority of the market on the same one. This variation of the theory together with the appearance of the “neoinstitucionalismo”, constitute the basic changes of the model… and the necessary conceptual elements for the transformation of the capitalism in the world.